How to determine the centre of mass of bodies from image modelling. (13th January 2016) - Dias, Marco Adriano; Carvalho, Paulo Simeão; Rodrigues, Marcelo
Abstract: Image modelling is a recent technique in physics education that includes digital tools for image treatment and analysis, such as digital stroboscopic photography (DSP) and video analysis software. It is commonly used to analyse the motion of objects. In this work we show how to determine the position of the centre of mass (CM) of objects with either isotropic or anisotropic mass density, by video analyses as a video based experimental activity (VBEA). Strobe imaging is also presented in an educational view, helping students to visualize the complex motion of a rigid body with heterogeneous structure. As an example, we present a hammer tossed with translation and rotation. The technique shown here is valid for almost any kind of objects and it is very useful to work with the concept of CM.